2019
DOI: 10.3390/foods8120682
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nutritional, Physicochemical, and Phytochemical Composition and Antioxidant Capacity of Three Strawberry “Fragaria × ananassa Duch.” Cultivars (“Primoris”, “Endurance”, and “Portola”) from Western Region of Portugal

Abstract: In this study, nutritional composition (protein, lipids, carbohydrates, ash, and moisture), physicochemical properties (soluble solid content, titratable acidity, texture and instrumental colour on surface, and internal section), phytochemicals (total phenolic content and anthocyanin content), and antioxidant capacity (DPPH-2,2 -diphenyl-1-picrylhydrazyl radical scavenging capacity and ferric-reducing antioxidant power) of three strawberry (Fragaria × ananassa Duch.) cultivars (cv. "Primoris", cv. "Endurance",… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 48 publications
(59 reference statements)
1
26
0
Order By: Relevance
“…These results agree with values previously reported in other strawberry cultivars [36][37][38]. For example, Ganhão et al (2019) [39] described similar result respect to the red color in the ripe stages of three cultivars from western Portugal region ("Primoris," "Endurance," and "Portola"). These authors showed that for a* values of whole strawberry fruits, no significant differences were found in any of the cultivars, which revealed a similar redness.…”
Section: Color Development and Color Qualitysupporting
confidence: 91%
See 3 more Smart Citations
“…These results agree with values previously reported in other strawberry cultivars [36][37][38]. For example, Ganhão et al (2019) [39] described similar result respect to the red color in the ripe stages of three cultivars from western Portugal region ("Primoris," "Endurance," and "Portola"). These authors showed that for a* values of whole strawberry fruits, no significant differences were found in any of the cultivars, which revealed a similar redness.…”
Section: Color Development and Color Qualitysupporting
confidence: 91%
“…Finally, a recent study showed that total phenolic content of three different cultivars from western Portugal region displays significant differences ranging from 607 to 1314 mg GAE/100 g [39]. In the case of the cultivars produced in Portugal, "Portola" showed the lowest value of total phenolic content with 605.698 mg GAE/100 g; meanwhile, "Primoris" and "Endurance" display 942 and 1314 mg GAE/100 g, respectively [39]. Now, and even though the phenolic content of strawberry described depends on location and the time of year production, our results are in accordance with Ganhão et al (2019) [39], who describe "Portola" as the cultivar with the lowest phenolic content of the three cultivars analyzed.…”
Section: Total Phenolic Flavonoid and Anthocyanin Contentmentioning
confidence: 97%
See 2 more Smart Citations
“…Besides carbohydrates, starch also can be found as an important element in this tuber [3,4]. Moreover, the health-promoting effects associated with the consumption of sweet potato have been attributed to the abundance of nutrient compositions, including protein, dietary fiber, and vitamin C [4,5]. Therefore, the increased production of this tuber has been associated not only with high consumer acceptance due to its sensory attributes but also with the presence of beneficial biochemical composition for consumer health, such as anti-inflammatory and anti-oxidative compounds [6].…”
Section: Introductionmentioning
confidence: 99%